Effectiveness of clear aligners in achieving proclination and intrusion of incisors among Class II division 2 patients: a multivariate analysis - Xinyu Yan; Xiaoqi Zhang; Linghuan Ren; Yi Yang; Qingxuan Wang; Yanzi Gao; Qingsong Jiang; Fan Jian; Hu Long; Wenli Lai (SpringerOpen, 2023)
Abstract Background The predictability of incisor movement achieved by clear aligners among Class II division 2 patients is poorly understood. The aim of this retrospective study was to determine the effectiveness of clear aligners in proclining and intruding upper incisors and its influencing factors. Methods Eligible patients with Class II division 2 malocclusion were included. For clear aligner therapy, three types of incisor movements were designed: proclination, intrusion and labial movement. Pre-treatment and post-treatment dental models were superimposed. The differences between predicted and actual (DPA) tooth movement of incisors were analyzed. Univariate and multivariate linear regression were used to analyze the potential influencing factors. Results A total of 51 patients and their 173 upper incisors were included. Actual incisor proclination and intrusion were less than predicted ones (both P < 0.001), while actual labial movement was greater than predicted one (P < 0.001). Predictability of incisor proclination and intrusion was 69.8% and 53.3%, respectively. Multivariate linear regression revealed that DPA of proclination was significantly positively associated with predicted proclination (B = 0.174, P < 0.001), ipsilateral premolar extraction (B = 2.773, P < 0.001) and ipsilateral canine proclination (B = 1.811, P < 0.05), while negatively associated with molar distalization (B = − 2.085, P < 0.05). The DPA of intrusion was significantly positively correlated with predicted intrusion (B = 0.556, P < 0.001) while negatively associated with labial mini-implants (B = − 1.466, P < 0.001). The DPA of labial movement was significantly positively associated with predicted labial movement (B = 0.481, P < 0.001), while negatively correlated with molar distalization (B = − 1.004, P < 0.001), labial mini-implants (B = − 0.738, P < 0.001) and age (B = − 0.486, P < 0.05). Conclusions For Class II division 2 patients, predicted incisor proclination (69.8%) and intrusion (53.3%) are partially achieved with clear aligner therapy. Excessive labial movement (0.7 mm) of incisors may be achieved. Incisor movement is influenced by predicted movement amount, premolar extraction, canine proclination, molar distalization, mini-implants and age.